Profile of ipilimumab and its role in the treatment of metastatic melanoma - Patel SP; Woodman SE (Dove Medical Press, 2011)
Sapna P Patel, Scott E WoodmanMelanoma Medical Oncology Department, University of Texas, MD Anderson Cancer Center, Houston, TX, USAAbstract: Melanoma is an immunogenic cancer. However, the ability of the immune system to eradicate melanoma tumors is affected by intrinsic negative regulatory mechanisms. Multiple immune-modulatory therapies are currently being developed to optimize the immune response to melanoma tumors. Two recent Phase III studies using the monoclonal antibody ipilimumab, which targets the cytotoxic T-lymphocyte antigen (CTLA-4), a negative regulator of T-cell activation, have demonstrated improvement in overall survival of metastatic melanoma patients. This review highlights the clinical trial data that supports the efficacy of ipilimumab, the immune-related response criteria used to evaluate clinical response, and side-effect profile associated with ipilimumab treatment.Keywords: ipilimumab, melanoma, T-cells, CTLA-4